Risk Management at the Institute of Chemistry of the State University of Rio De Janeiro - Sara F.D. Bueno; Marco A.G. Figueiredo (Chemical Engineering Transactions, 2023)
The present work aims to evaluate the perception of students in relation to the risk of activities carried out in the laboratories (academic and research) of the Institute of Chemistry of the State University of Rio de Janeiro. In laboratories, equipment operating under pressure and hazardous chemical compounds can harm human health or result in accidents, some fatal. Risk assessments were carried out in the laboratories, using nationally accepted risk management standards, to identify the risks that the laboratories are exposed to in relation to fire and explosion safety, as well as to understand the history, causes and consequences of previous accidents. In a simplified way, it was concluded that the perception of risk by students and employees of the Institute of Chemistry is low. Thus, the need for improvements in laboratories was pointed out, to mitigate or eliminate existing risks, in addition to help foster a strong safety culture, through which laboratory risks can be identified and properly managed by all working in such environments. Consequently, the frequency and severity of laboratory accidents is expected to be reduced or even eliminated.